DOSAGES ANALYSIS OF HYPERBARIC OXYGEN THERAPY TO IMPROVING COGNITIVE FUNCTION IN PATIENTS POST-TRAUMATIC BRAIN INJURY: A REVIEW - Nuri, Almas; Edi, Djatiwidodo; Anindya, Pramita; Ilmawan, Moh. Fathi (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2025)
Background: Traumatic brain injury is a type of intracranial injury caused by a mechanical impact that causes anatomical and physiological damage to the brain. Globally, there are 50 million cases of traumatic brain injury each year that cause 10 million deaths and/or hospitalizations. Hyperbaric oxygen therapy is a therapy that uses 100% oxygen at pressures greater than 1 Atmosphere Absolute (ATA) to increase tissue oxygenation and repair damaged tissue. This study was made to determine the effect of hyperbaric oxygen therapy on improving cognitive function in post-traumatic brain injury patients and the mechanisms underlying it. Objective: To determine the dose of hyperbaric oxygen therapy that can trigger improved cognitive function in post-traumatic brain injury patients, as well as the side effects. Methods: This research is descriptive research and uses the literature study method. In collecting data, using all journals with the search keywords